Auroras: A Harmonious Blend of Natural Science and Human Culture - Belay Sitotaw Goshu; Muhammad Ridwan (Britain International for Academic Research (BIAR-Publisher), 2024)
Since ancient times, auroras have fascinated science and religion because of their amazing natural displays in Earth's upper atmosphere. With an emphasis on the recombination and diffusion of ions during auroral events, this study investigates the ionospheric processes in the E-region and syndicates the results with spiritual and cultural interpretations. The study sought to understand the scientific and spiritual significance of these processes by examining changes in ion concentrations with altitude and time. Through analytical and numerical simulations, the study found that during the day, A+ ion recombination is more active between 80 and 120 km altitude, with diffusion from 1e6 to 2.4 × 105 cm-3. Recombination rates for A+ ions rise at night, but those for B atoms drop, especially in the region between 100 and 120 kilometers above sea level. These findings are important for comprehending how space weather affects navigation and communication systems. Spiritually speaking, auroras are said to be cosmic occurrences that represent heavenly messages or ancestors' souls. The amalgamation of scientific analysis and cultural narratives yields a more comprehensive and multifaceted comprehension of auroral events. The study concludes that integrating spiritual viewpoints with scientific investigation improves our understanding of natural occurrences. To preserve indigenous tribes' perceptions of auroras, recommendations include fostering interdisciplinary research, introducing cultural narratives into educational initiatives, and interacting with them.